Turkish prospective teachers' images of the constructivist view of teaching: are they compatible with the epistemological foundations of constructivism? - KABAPINAR, YÜCEL (ELSEVIER SCIENCE BV, 2010)
This study aimed to find out how the prospective teachers visualize constructivist view of learning. It also aimed to uncover their reasoning behind their image for constructivist view. The study was designed with the qualitative research method. The study conducted with 4(th) grade prospective teachers employed a total of 226 participants from classroom teacher and chemistry departments. They were provided a caricature on the transmission view of learning and asked to make a caricature to represent the constructivist view of learning together with its explanation. The results of the analysis of the prospective teachers' drawings and explanations indicated that the prospective teachers' visualization involves five features of the constructivist view. These were related to learners' role, teachers' role, philosophy of constructivist view, instructional materials and learner's acquirements. The findings also showed that in their visualisation there were both common and different elements of constructivism. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Constructivism; caricature; prospective teachers; Turkish; elementary; science; LEARNING ENVIRONMENTS; BELIEFS